2021
DOI: 10.3390/ijerph182111014
|View full text |Cite
|
Sign up to set email alerts
|

Policymakers’ Research Capacities, Engagement, and Use of Research in Public Health Policymaking

Abstract: The use of research in public health policymaking is one of the prerequisites for successfully implemented health policies which have better population health as an outcome. This policy process is influenced by the actors involved under the policy umbrella, with inter-related contextual factors and specific structural and institutional circumstances. Our study investigates how policymakers’ research capacities influence the use of research in the health policy process and identify areas where capacity-building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 64 publications
3
15
0
Order By: Relevance
“…To further improve best practice assessments, we suggest involving policymakers more extensively in the assessment process. This could include their participation in either the development or upgradation of the criteria and during the actual assessment process ( 36 ). While researchers may prefer to maintain independence from policymaking and implementation, public health research can have the most significant impact when researchers, practitioners, and decision-makers take responsibility for its production and application ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further improve best practice assessments, we suggest involving policymakers more extensively in the assessment process. This could include their participation in either the development or upgradation of the criteria and during the actual assessment process ( 36 ). While researchers may prefer to maintain independence from policymaking and implementation, public health research can have the most significant impact when researchers, practitioners, and decision-makers take responsibility for its production and application ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this funding was depicted as inadequate. Various studies have identified the inadequacy of funding for research as a major barrier to institutional evidence generation and use in Nigeria and other LMICs [ 17 , 23 , 26 , 39 ]. These findings underscore the need for institutional prioritization and commitment to research evidence generation measured primarily by the amount of local funding made available for research.…”
Section: Discussionmentioning
confidence: 99%
“…Partnerships between researchers and policy-makers have been found to be suboptimal, with many identified barriers to effective knowledge translation and use of research evidence in decision-making by policy-makers. [ 21 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“… 35 Further, capacity building to increase research use and collaboration in evidence-informed policy making among policy makers was proposed. 36 …”
Section: Discussionmentioning
confidence: 99%
“…35 Further, capacity building to increase research use and collaboration in evidence-informed policy making among policy makers was proposed. 36 The process of decision making varies by context, content, and actors 37,38 and their attributes such as legitimacy, power, and interest. 39 Actors can either support or not support the policy under consideration.…”
Section: What Capacities Are Required?mentioning
confidence: 99%